Mathematical model of cutting process of cutting tools with a side-mounted multifaceted, requiring no sharpening plates - Nastasenko, V.À.; Babiy, M.V.; Protsenko, V.O. (Ye.A.Buketov Karaganda State University Publ., 2018)
The article presents the results of experimental research of the cutting process with cuto˙ tools with laterally mounted multifaceted unresharpenable plates (MUP), which allowed to confirm their eÿciency and progressiveness. As a result of research and experimental data processing, for the first time, the mathematical models were obtained that adequately describe force parameters (Pz and Py) of cutting process by the proposedcuto˙ tools. The rational values of rake and relief angles are determined.
Бүйірлі орнатылған көпқырлы қайралмайтын пластиналарды кесілген кескіштермен кесу процесінің математикалық моделі
Математическая модель процесса резания отрезными резцами с боковой установкой многогранных неперетачиваемых пластин
Keywords: assembled cutoff tool; multifaceted unresharpenable plate; mechanical mounting